2008
DOI: 10.21273/horttech.18.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Onion Variety Response to Iris Yellow Spot Virus

Abstract: Onion (Allium cepa) varieties for commercial production in eastern Oregon and southwestern Idaho are evaluated annually in replicated trials conducted at the Malheur Experiment Station, Oregon State University, near Ontario, Oregon. Characteristics evaluated include bulb yield, market grade, and the frequency of single centers. After the emergence of iris yellow spot virus (IYSV) as a threat to commercial onion production in the early 2000s, onion varieties at the Malheur Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…One of the major impacts of IYSV on onion bulb yields is downgrading of bulb size, rather than a decrease in the number of bulbs ( 11,16,47). Onion bulbs that are misshapen, rotten, or too small to be marketable are removed during the grading process and disposed of in cull piles.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major impacts of IYSV on onion bulb yields is downgrading of bulb size, rather than a decrease in the number of bulbs ( 11,16,47). Onion bulbs that are misshapen, rotten, or too small to be marketable are removed during the grading process and disposed of in cull piles.…”
Section: Discussionmentioning
confidence: 99%
“…Multani et al (2009) identified several entries, NMSU 03-52-1, NMSU 04-41, NMSU 04-44-1, and 'NuMex Jose Fernandez', that expressed fewer IYS symptoms than other entries. Shock et al (2008) found that 'Joaquin', 'Charismatic', and 'Affirmed' expressed some of the lowest IYSV ratings over a 2-year period. Schwartz et al (2005) reported significant differences for IYSV incidence among onion cultivars when IYSV incidence ranged from 16% to 100% in 2003100% in and 13% to 61% in 2004100% in .…”
mentioning
confidence: 88%
“…Onion thrips is an important insect pest of onion causing direct damage to leaves and stored bulbs (Alston and Drost, 2008), reduced bulb and seed yields (Elmore, 1949;Jones et al, 1934), and transmission of serious pathogens such as iris yellow spot virus (Gent et al, 2004;Shock et al, 2008). Effective control of onion thrips necessitates frequent insecticide applications (Alston and Drost, 2008) with the unfortunate result of increased resistance to commonly used chemicals (Allen et al, 2005;Herron et al, 2008;Shelton et al, 2006).…”
mentioning
confidence: 99%